"Rhenium Ionnini SorbtsionSpectroscopic Creation Of Detection Technology" - Mirzakhmedov Rustamjon Mirhamidovich; Madusmanova Nazira Kuchkarbaevna; Miradhamova Gulyorkhan Otkir daughter (Genius Journals, 2023)
To find the mechanism of immobilization of the vismutol-2 Reagent on the carrier, and to determine the optimal conditions for their formation of a complex with the rhenium (III) ion, and metrological properties have been developed. The sorbtsion – spectroscopic method with high sensitivity and selectivity for determining the rhenium (III) ion has been shown. The developed sorption – spectroscopic method was applied to Real objects (industrial waste technological waters and cakes), the results were processed by the method of Mathematical Statistics and data were given on its application in the analysis.
Keywords: Rhenium; ions; bismutol; immobilization